Extending the Frontiers of Financial Development for Sustainability of the MENA States : The Roles of Resource Abundance and Institutional Quality - Onifade, Stephen Taiwo; Gyamfi, Bright Akwasi; Haouas, Ilham; Asongu, Simplice A. (John Wiley & Sons, 2023)
Resource abundance characterizes economies within the MENA region from North Africa to the Middle East. As such, to improve financial development (FD) for regional economic sustainability, this study provides a comprehensive analysis of the roles of natural resources abundance and institutional quality indicators on the region's FD while underscoring the inflationary levels and general economic growth trends amidst rising globalization. The adopted empirical strategy (CS-ARDL and AMG) is employed for potential cross-sectional dependency (CD) and slope homogeneity in the regional data spanning over two decades (2000–2020). Unlike the extant literature, two separate regional FD indicators were considered for an insightful analysis namely, banking financial services via domestic credit to private sector, and financial stability via the Z-score values showing the tendencies of default in a country's banking structure. Regardless of the FD indicator, the results reveal that natural resources, growth trends, and inflationary levels significantly spur long-run regional FD thereby invalidating the financial resource curse hypothesis in the region. Furthermore, both institutional quality levels and globalization produced detrimental impacts on FD levels. However, the interaction between institutional quality levels and natural resources shows a desirable FD-stimulating effect in the region, noticeably when FD is proxied by the Z-score. Thus, implying that stronger institutions are crucial for MENA's overall financial stability vis-à-vis reduction in the risk of default in the banking system. Hence, policy recommendations including the strengthening of institutional capacities among others, were suggested to regional authorities toward harnessing resources for sustainable regional FD.
Keywords: financial development; institutions; MENA region; sustainable growth; natural resources; fi=Taloustiede|en=Economics|